Aplikasi Manajemen Kegiatan Kemahasiswaan STIKI Indonesia Berbasis WEB (LP2M INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2018)
STMIK STIKOM Indonesia is one of Information Technology University of Bachelor Degree's in Bali. It is concerned on providing the ultimate service for the students. The comfortable of students can be achieved through the information services of lecturing and student activities are provided by campus. Student activity is the most important activity in order to support student soft skills, and to fulfill graduation requirements of participation credit Score, it is shortened by SKP. Problems that occur at this time recording student activities and the use of space is still done manually by using the blackboard, when it is carried out during the lecturing schedules, so that there are constraints on the use of room activities. The results of this study is an application that can provide kemudahaan in managing activities and use of space and facilitate students to obtain information on student affairs activities on campus